FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN PADA KELUARGA BURUH SAWIT HARIAN DI DESA WAWORAHA KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Ikhsan, Muhamad Nur; Peribadi, Peribadi; Tanzil, Tanzil (WELL-BEING: Journal of Social Welfare, 2023)
This study aims to identify the factors contributing to poverty within the households of daily palm oil laborers in Waworaha village, Palangga subdistrict, South Konawe district. Employing a qualitative descriptive research approach, the focus is on the challenges faced by palm oil workers associated with PT. Merbau Jaya Indah Raya. The research comprises 8 informants, individuals from Waworaha village employed as palm oil workers at PT Merbau Jaya Indah Raya. The findings reveal various factors influencing poverty among the families of palm oil workers in Waworaha Village. Firstly, a significant factor is the low educational attainment, evident in the predominant completion of education up to junior high school in Southeast Sulawesi. This limited educational background poses challenges in securing better employment opportunities. Secondly, the constrained availability of natural resources plays a crucial role in meeting essential human needs when appropriately harnessed. However, the proper utilization of these resources remains a challenge. Thirdly, the restricted employment options further exacerbate the situation. Individuals in Waworaha Village often find themselves limited to working as palm oil laborers at PT Merbau Jaya Indah Raya, with uncertain daily wages. The limited job market, particularly coupled with lower educational qualifications, confines them to this occupation. Lastly, the issue of low wages is significant, particularly for those engaged as daily laborers. In Waworaha Village, some individuals working at PT Merbau Jaya Indah Raya face financial hardships due to meager wages, making it challenging to sustain their daily lives.